2018
DOI: 10.1021/acsomega.8b01252
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrogen-Doped Nanoporous Carbon Nanospheroids for Selective Dye Adsorption and Pb(II) Ion Removal from Waste Water

Abstract: In the presence of melamine and block copolymers, namely, F108, F127, and P123, nitrogen-doped nanoporous carbon nanospheroids (N@CNSs) were synthesized by the hydrothermal process. The F127-modified sample (CNF127) exhibits the maximum Brunauer–Emmett–Teller (BET) surface area of 773.4 m 2 /g with a pore volume of 0.877 cm 3 /g. The microstructural study reveals that nanospheroids of size 50–200 nm were aggregated together to form a chainlike structure for all tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
(58 reference statements)
1
41
0
Order By: Relevance
“…On the other hand, the sp 3 -hybridized nitrogen element affords adequate lone pair electrons to form the complex compound structure with transition-metal ions such as Cu 2+ and Ni 2+ . Also, this mechanism could also explain why amino-Fe 3 O 4 @C- x -O samples have higher adsorption capacity toward transition-metal ions than other metallic ions. , …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the sp 3 -hybridized nitrogen element affords adequate lone pair electrons to form the complex compound structure with transition-metal ions such as Cu 2+ and Ni 2+ . Also, this mechanism could also explain why amino-Fe 3 O 4 @C- x -O samples have higher adsorption capacity toward transition-metal ions than other metallic ions. , …”
Section: Resultsmentioning
confidence: 99%
“…However, when the concentration of Pb 2+ exceeds 50 mM, the adsorption capacity of Alg-PAM remains stable and shows no further increase. Therefore, the maximum adsorption capacity of Alg-PAM for Pb 2+ is 252.2 mg/g, which is higher than that of most of the reported Pb 2+ sorbents (Table 2) [28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Adsorption Performance Of Alg-pam For Metal Ionsmentioning
confidence: 95%
“…[34] The positive values of ΔS 0 indicated that the randomness increased at the solid/liquid interface. [45] NiFe 2 O 4 /MnO 2 nanocomposites 85.78 [46] PVC/α-MnO 2 -KH550 NC 5% wt% 100 [14] Manganese-oxide/biochar 91.98 [47] Fe 3 O 4 -g-C 3 N 4 189.36 [48] S 3.9% -g-C 3 N 4 52.63 [49] CNF 127 99.82 [50] Sugar cane biochar 86.96 [51] Graphene oxide-starch 108.68 [52] g-C 3 N 4 65.6 [53] g-C 3 N 4 /β-CD 100.5 [54] These results demonstrated that the adsorption process of Pb (II) onto g-C 3 N 4 /MnO 2 was spontaneous and endothermic.…”
Section: Thermodynamic Studiesmentioning
confidence: 99%